PHILOSOPHICAL AND LINGUISTIC ASPECTS OF THE NOTION OF ‘CONCEPT’ (AS EXEMPLIFIED BY THE CONCEPT OF ‘MEDICINE’ VERBALISATION IN ENGLISH MEDICAL DISCOURSE ) - A. A. Kharkovskaya; A. A. Golubyh (Дискурс профессиональной коммуникации, 2019)
Various philosophical and linguistic aspects of the notion of ‘concept’ are considered and exemplified by revealing and systematizing verbal markers of the concept of ‘medicine’ in English medical discourse. The present research is motivated by the current renovations within the modern medical paradigm and by the application of new medical terms registered both in dictionaries or reference books for medical professionals and in popular newspaper articles. The adequate interpretation of different visions of the notion of ‘concept’ in the classical studies by linguistic and philosophical authors contributes to identifying the key verbal characteristics of the concept of ‘medicine’ in English discourse. The analysis of lexicographic discourse reveals the semantic parameters of medical terminological markers according to which they are grouped into monosemantic and multivalued language units. Furthermore, the etymological aspects of the verbal units under consideration are also described. Multivalued terminological units are characterized by a significant semantic potential and are considered as a reliable basis for further semantic development of modern English vocabulary. Within the English educational discourse, the concept of ‘medicine’ is verbalized by medical linguistic markers concerning proper nutrition, daily schedule and health destructive factors. The studies of media resources referring to the concept of ‘medicine’show that advertising of medical treatment or pills providing for a healthy life-style is usually accompanied by anti-advertising of medical products harmful for human health. The description of medical terms within the frames of lexicographic, educational, and massmedia sources contributes to a valid interpretation of the ‘medicine’ concept in modern English worldview, which is of vital importance today since valid comprehension of modern medical problems in terms of its successes and failures contributes to effective critical thinking training schemes and further development of both national and international philosophical culture.